Hello goodbye dog - Gianferrari, Maria; Barton, Patrice, 1955- (New York : Roaring Brook Press, 2017)
A student who uses a wheelchair finds a way to see her dog each day in school.
Keywords: Dogs -- Fiction; Schools -- Fiction; People with disabilities -- Fiction; Whelchairs -- Fiction; JUVENILE FICTION / Animals / Dogs; JUVENILE FICTION / School & Education; JUVENILE FICTION / Social Issues / Special Needs